Pengarahan Pengelolaan Sosial Media dan Pembuatan Konten TikTok di Desa Wisata Dieng Kulon - Adhityawarman, Benediktus; Octavanny, Vitha; Zagita Sahra; Muhammad Fariz Arzad; Muhammad Dzaky Arrauf (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
Briefing on Social Media Management and Content Creation TikTok at Dieng Kulon Tourism Village The development of technology allows everyone to use it for various purposes, one of which is promotion. The use of social media for promotional media has a big influence on the products offered because of the wide reach of social media. Dieng Kulon Tourism Village, which does not yet have a special social media for the village, is an opportunity for the Pancasila University Tourism Faculty to carry out this service. The purpose of this activity is to provide assistance to tourism awareness groups and village youth groups on how to manage social media accounts and create content for village promotional media. The initial method is preparation and planning in the form of group discussions with Pokdarwis Dieng Kulon Tourism Village, social media practitioners, lecturers, and discussions between members. The implementation of this community service is to provide material exposure regarding social media management and TikTok content creation. And evaluation in the form of giving pre-test and post-test. The results obtained are in the form of increased understanding of social media account management and content creation, especially TikTok.